The possibility dogs : what a handful of "unadoptables" taught me about service, hope, and healing - Charleson, Susannah (Houghton Mifflin Harcourt, 2013)
A tour of the psychiatric service dog industry traces the author's work with unwanted shelter dogs before matching them with people in need, documenting her own partnership with a search canine while sharing uplifting success stories.